2009
DOI: 10.1080/10410230902889225
|View full text |Cite
|
Sign up to set email alerts
|

Influences on Health Delivery System Satisfaction: A Partial Test of the Ecological Model

Abstract: This study uses structural equation modeling to investigate several predictors of hospital system satisfaction. Drawing on Street's ecological perspective, the researchers explore several individual, provider-patient interaction, and system perceptions and expectations, test a model of hospital system satisfaction, and discuss the implications of the structural equation modeling analysis. Specifically, it was hypothesized that individuals who rated themselves as having high self-efficacy would report higher le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 52 publications
0
19
2
Order By: Relevance
“…Effective communication between health professionals and their clients is a critical part of healthcare [1], [2], [3]. Poor communication in the health context can result in adverse outcomes for patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…Effective communication between health professionals and their clients is a critical part of healthcare [1], [2], [3]. Poor communication in the health context can result in adverse outcomes for patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, previous research (Koemer & Kilbane, 2008;Moore et al, 2009;& Uitterhoeve et al, 2009) conducted in traditional healthcare settings (off-campus) found that affective behavior had a stronger association with patient satisfaction than instrumental behavior.…”
Section: Summary Of Findingsmentioning
confidence: 92%
“…A large body of research has examined the influence of health provider-patient communication on patient satisfaction (Dutta-Bergman, 2005;Moore, Wright, & Bernard, 2009). Moore, Wright, and Bernard (2009) suggest that patients may not be educated enough to be able to evaluate physicians' technical or task behaviors but may be able to evaluate physicians' affective behaviors such as patience, concern, empathy, and attentiveness. Consequently, most scholarships deal with the association between influence of affective behaviors and patient satisfaction.…”
Section: Patient Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations